Предмет: Геометрия,
автор: hucantamada
LQ (-8:16) Q(4:4) L(x, y) -?
Ответы
Автор ответа:
0
Ответ:
Объяснение:
Решение: y'=( lq^3(x^2) )'=3*lq^2(x^2)*( lq (x^2))’= 3*lq^2(x^2)\ (ln 10 *x^2)* (x^2)’=
3\ln 10 *2x\x^2 * lq^2(x^2)=6\(x*ln 10) * lq^2(x^2).
по правилу взятия производной от сложной функции и производных элементарных функций
Ответ: 6\(x*ln 10) * lq^2(x^2)
Похожие вопросы
Предмет: Алгебра,
автор: katabahmet83
Предмет: Химия,
автор: 29vladko2009
Предмет: География,
автор: romanecmaria7
Предмет: Английский язык,
автор: Skryinnikovaalina200
Предмет: Литература,
автор: ren81